The influence of teaching presence on students satisfaction toward mooc based flipped classroom - Gao JiMei; Mad Noor Madjapuni; Tan, Choon Keong (Secholian Publication, 2024)
Student satisfaction plays a crucial role in ensuring effective flipped learning. This study designed a flipped "Fundamentals of Computer Application (FCA)" course based on Chaoxing MOOC platform and investigated 442 students' satisfaction with the model and the relationship between teaching presence and students satisfaction. The results showed that student satisfaction with the model was high (M = 19.37, SD = 2.694, total 129 in the affective coding, of which 79 were positive and only 2 were negative), and that the three dimensions of Teaching Presence(TP), Instructional Design and Organization(IDS) (r = 0.410, p < .001), Facilitated Discourse (FD) (r = 0.355, p < .001), Direct Instruction (DI) (r = 0.362, p < .001) were all positively and significantly related to satisfaction, with Instructional Design and Organization(IDS) (β = .239, t = 4.555, p = < .001) , and Direct Instruction (DI) (β = .218, t = 2.468, p = < .05) were able to significantly predict satisfaction. The findings indicated that students are highly satisfied with the flipped model in the FCA course, which is mainly practical and hands-on. Consequently, teachers should carefully plan and organize their lessons, give students direct guidance when needed, foster a safe learning environment, and provide more opportunities for students to give speeches. All of these strategies will contribute to students' increased satisfaction with flipped learning.